Ponatinib versus imatinib for newly diagnosed chronic myeloid leukaemia: an international, randomised, open-label, phase 3 trial. Issue 5 (May 2016) - Lipton, Jeffrey H; Chuah, Charles; Guerci-Bresler, Agnès; Rosti, Gianantonio; Simpson, David; Assouline, Sarit; Etienne, Gabriel; Nicolini, Franck E; le Coutre, Philipp; Clark, Richard E; Stenke, Leif; Andorsky, David; et al.
Summary: Background: Ponatinib has shown potent activity against chronic myeloid leukaemia that is resistant to available treatment, although it is associated with arterial occlusion. We investigated whether this activity and safety profile would result in superior outcomes compared with imatinib in previously untreated patients with chronic myeloid leukaemia. Methods: The Evaluation of Ponatinib versus Imatinib in Chronic Myeloid Leukemia (EPIC) study was a randomised, open-label, phase 3 trial designed to assess the efficacy and safety of ponatinib, compared with imatinib, in newly diagnosed patients with chronic-phase chronic myeloid leukaemia. Patients from 106 centres in 21 countries were randomly assigned (1:1, with stratification by Sokal score at diagnosis) using an interactive voice and web response system to receive oral ponatinib (45 mg) or imatinib (400 mg) once daily until progression, unacceptable toxicity, or other criteria for withdrawal were met. Eligible patients were at least 18 years of age, within 6 months of diagnosis, and Philadelphia chromosome-positive by cytogenetic assessment, with Eastern Cooperative Oncology Group performance status of 0–2, and had not previously been treated with tyrosine kinase inhibitors. The primary endpoint was major molecular response at 12 months. Patients who remained on study and had molecular assessments at specified timepoints were studied at those timepoints. Safety analyses included all treated patients, as per study protocol. This trial is registered withClinicalTrials.gov, numberNCT01650805 . Findings: Between Aug 14, 2012, and Oct 9, 2013, 307 patients were randomly assigned to receive ponatinib (n=155) or imatinib (n=152). The trial was terminated early, on Oct 17, 2013, following concerns about vascular adverse events observed in patients given ponatinib in other trials. Trial termination limited assessment of the primary endpoint of major molecular response at 12 months, as only 13 patients in the imatinib group and ten patients in the ponatinib group could be assessed at this timepoint; the proportion of patients achieving a major molecular response at 12 months did not differ significantly between the two groups (eight [80%] of ten patients given ponatinib and five [38%] of 13 patients given imatinib; p=0·074). 11 (7%) of 154 patients given ponatinib and three (2%) of 152 patients given imatinib had arterial occlusive events (p=0·052); arterial occlusive events were designated serious in ten (6%) of 154 patients given ponatinib and in one (1%) of 152 patients given imatinib (p=0·010). The data monitoring committee criterion for risk assessment (significant difference in serious grade 3 or 4 ischaemic events between groups) was not met (five [3%] of 154 vs one [1%] of 152; p=0·21). Grade 3 or 4 adverse events observed in more than 5% of patients in the ponatinib group were increased lipase (22 [14%] of 154 vs three [2%] of 152 with imatinib), thrombocytopenia (19 [12%] of 154 vs ten [7%] of 152 with imatinib), rash (ten [6%] of 154 vs two [1%] of 152 with imatinib). In the imatinib group, grade 3 or 4 adverse events observed in more than 5% of patients were neutropenia (12 [8%] of 152 vs five [3%] of 154 with ponatinib) and thrombocytopenia (ten [7%] of 152 vs 19 [12%] of 154 with ponatinib). Serious adverse events that occurred in three or more patients given ponatinib were pancreatitis (n=5), atrial fibrillation (n=3), and thrombocytopenia (n=3). No serious adverse event occurred in three or more patients given imatinib. Interpretation: The efficacy of ponatinib treatment of newly diagnosed chronic-phase chronic myeloid leukaemia compared with imatinib could not be assessed due to trial termination, but preliminary data suggest there might be benefit, although with more arterial occlusive events than with imatinib at the doses studied. Because the EPIC trial was terminated early, efficacy of ponatinib in this setting remains to be established. Funding: ARIAD Pharmaceuticals.